Warning: Medical education is hazardous to your mental health. Medical students should make an informed decision to begin and continue training - Stacey, Adam; D'Eon, Marcel; Andersen, Melissa; Koehncke, Niels; Campoli, Jessica; Thompson, Galilee; Riou, Kylie (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
For decades there has been ample evidence that training to become a physician and practicing medicine is hazardous to one’s health and wellness. In the face of the extremely high rates of suicide, substance abuse, depression and burnout in the medical student, resident, and physician populations, it would be dishonest to suggest medical education and practice is all gain and no pain. This article is directed to members of the medical education community and challenges stakeholders to view their teaching and training of medical students as an intervention requiring free and informed consent. We hope this exercise shifts the paradigm of educators and enables students to enter medical training from a free and informed position.